Patellar Tendon Debridement and Reconstruction With Hamstring Tendon Autografts in the Setting of Severe Patellar Tendinopathy - Evan P. Shoemaker BA; Luke V. Tollefson BS; Erik L. Slette MD; Robert F. LaPrade MD, PhD (SAGE Publishing, 2024)
Background: Patellar tendinopathy is a multifactorial condition characterized by micro-degenerative changes in the patellar tendon. This results from repeated stress to the knee extensor mechanism from explosive movement, axial malalignment, and/or abnormal patellar height. Currently, there is no standard surgical procedure for the treatment of severe patellar tendinopathy. Indications: Patellar tendon reconstructions for patellar tendinopathy may be indicated when >50% of the tendon attachment is degenerative and detached from the distal patella and non-operative treatment, like physical therapy, bracing, and injections, have not relieved symptoms. Debridement may not offer long-term viability against augmentation of the patellar tendon with autografts, with a risk of recurrent breakdown of the patellar tendon attachment with resumption of previous activities that initially lead to overload. Technique Description: An anterior incision was made from the superior pole of the patella to the tibial tubercle. Then, dissection was performed medially to harvest the gracilis and semitendinosus tendons. Open harvesters were used, and the hamstring tendons were released proximally, keeping the tibial insertions attached. A horizontal pin was drilled across the tibial tubercle and reamed with a 4.5 mm reamer. A passing stitch was fed through the tunnel. The proximal and distal margins of the patella were localized with spinal needles and a pin was drilled across its midportion, 5 mm deep to the dorsal cortical margin, and then rearmed. Degenerative tissue at the patellar tendon was excised. The gracilis tendon was passed medial to lateral through the tibial tubercle, and a Q-Fix anchor anchored the grafts medially and laterally. The semitendinosus graft was passed medial to lateral through the patella followed by the gracilis tendon lateral to medial. Appropriate reconstruction graft tension was confirmed and grafts were whipstitched together. Results: Clinical outcomes for the debridement of severe patellar tendinopathy report 77% symptomatic relief. With many unable to return to activity, patellar tendon reconstruction can be indicated. Outcomes for reconstructions for severe patellar tendinopathy are not reported. Discussion: Patellar tendon reconstruction with hamstring autografts for the treatment of severe patellar tendinopathy can provide a strong reconstruction graft to allow for the resumption of high-level activities. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.